Foreign Aid and Domestic Revenue Mobilization in Conflict-affected Countries - Maïmouna Diakite; Souleymane Diarra; Sampawende J.-A. Tapsoba; Tertius Zongo (Fondation pour les études et recherches sur le développement international (FERDI), 2019)
In recent years, there has been increasing interest in the impact of conflict on taxation, and a few articles have focused on aid effectiveness in conflict-affected countries. Both aid and conflict have been identified as major determinants of tax performance, however there is little agreement on the nature of their individual and joint effects on taxation. This study contributes to this debate by considering a sample of 123 developing countries over the period 1984 to 2014. Our findings show that aid granted during a period of conflict positively affects revenue collection, and this impact increases with technical assistance. A deeper analysis demonstrates a non-linear relationship between aid provided during conflict times and domestic revenue mobilization. The institutional environment appears to be a factor that may mitigate, and even reverse, the nature of the relationship between aid and revenue mobilization.
Keywords: D74; F35; H20; 330